Estoques e fluxos de carbono nas frações da matéria orgânica do solo nos agroecossistemas de roça de derruba-e-queima e roça melhorada(slash-and-mulch) - Alves, Rafaela Eloi de Almeida (2009)
The management of soil organic matter can be considered more important elements to agriculture sustainable in the tropics. The aim of this study was to evaluate fluxes and stocks of carbon in the fractions of the soil organic matter in slash-and-burn, secondary forest and slash-and-mulch areas. The experiments were carried out in smallholder farms in the Maranhão State, Brazil. Were evaluated: (i) the vegetation biomass in each area, (ii) the physical fractions of the soil organic matter, and (iii) the results ofsoil physical and chemistry analyses. The soil density was affected by total organic matter, which demonstrates a relationship with silt and clay fractions, increasing the macronutrients and pH of the first 10 cm of soil surface. The light fractions of soil organic matter were positive ly related with total organic matter, where these fractions presented a high average mineralization, which was evidenced after one year to the slash-and-burn agriculture, demonstrate like a sensitive physical indicator for changes in the soil management. The opposite was expected, the slashand-mulch area do not demonstrate significance in relation to increasing the organic matter (total and soil). The results demonstrated that the soil profile occur a decreasing in a total organic carbon stocks, besides until one meter depth observed an expression values (15,6 t.ha1 , 3 researched systems average), what can be evidenced an effective carbon sequestration until 1 meter of soil profile.